Simultaneous extraction of nickel, copper, and cobalt from low–grade nickel matte by oxidative sulfation roasting-water leaching process. (1st December 2021) - Xiao, Tengfei; Mu, Wenning; shi, Shuangzhi; Xin, Haixia; Xu, Xueqing; Cheng, Hao; Luo, Shaohua; Zhai, Yuchun
Highlights: 98.6% Ni, 93.4% Cu and 90.4% Co were co-extracted from low-grade nickel matte. The optimum conditions of extracting valuable metals and removing Fe were obtained. The transformation behavior of minerals in the sulfation process was determined. The sulfation roasting is proved to be an efficient and energy-saving method. Abstract: In the traditional nickel smelting process, low-grade nickel matte is converted into high-grade nickel matte through high-temperature smelting to oxidize iron and remove it as silicate slag. However, the process will result in a large amount of metal loss and the subsequent process of treating high-grade matte is complicated. This paper focuses on the simultaneous and direct extraction of Ni, Cu, Co from low-grade nickel matte by atmospheric oxidative sulfation roasting process, and then conducts selective calcination to remove iron. The effects of several factors, including roasting temperature, roasting time, matte particle size, mass ratio of acid to matte and oxygen injection rate, on the extraction of metals were investigated in the sulfation roasting process, and 98.6% Ni, 93.4% Cu and 90.4% Co can be extracted under the following conditions: roasting temperature is 220 °C, roasting time is 2 h, matte particle size is 160–180 mesh, mass ratio of acid to matte is 3:1, oxygen injection rate is 20 mL/min. The calcination temperature and time in the selective calcination process were studied to obtain appropriate iron removal condition, and approximately 44% Fe was removed under the other valuable metal extractions are constant. The advantages of this method are low reaction temperature, high reaction efficiency, and the tail gas generated in the whole process can be recycled and reused.